Developing the Competence of Accounting MGMP Teachers in Mojokerto Regency through Accurate Software Training to Meet the Needs of Industry and Business - Nugroho, Tatas Ridho; Izzalqurny, Tomy Rizky; Sanputra, Adrian Hartanto Darma; Dewanti, Nabila Aura; Aprilia, Riska Dwi (Institut Teknologi dan Bisnis Asia Malang, 2025)
Purpose: This program aims to improve the digital accounting competence of Accounting MGMP teachers in Mojokerto Regency through training in Accurate software, aligned with industry needs. Method: The program was implemented for all members of the Mojokerto Regency Accounting MGMP, totaling 15 teachers. Activities were conducted in four stages: preparation, training, implementation with CADE certification, and monitoring-evaluation using competency indicators. Practical Applications: Teachers gained hands-on experience integrating Accurate into lessons, supported by mentoring from practitioners to ensure alignment with DUDI standards. The training was conducted in a hybrid manner (offline at SMKN 1 Sooko and online via Zoom). Conclusion: The program successfully enhanced teachers’ skills in using digital accounting tools, improved teaching quality, and increased student readiness for the digital workforce. Results showed that 15 of 15 teachers (100%) passed the CADE certification, and 83% of students successfully completed the digital accounting assignments without significant errors. However, the study's scope was limited to a single district, and the use of paid software poses potential sustainability challenges. Implications of this study emphasize the need for replication strategies and educational licensing negotiations to expand the training's benefits sustainably.